Peningkatan Motivasi Belajar Siswa Melalui Penerapan Variasi Strategi Pengajaran Pembelajaran Berbasis Masalah (PBL) di Kelas IV UPTD SDN 075053 Fadoro Idanoi - Sitefanus Seferiman Gea (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Learning motivation is a crucial factor that influences the success of the learning process. Students with high learning motivation tend to be more active and engaged in learning activities, while those with low motivation often feel bored and less participative. In Grade IV of UPTD SDN 075053 Fadoro Idanoi, low learning motivation has become a problem that affects students' engagement and academic performance. The conventional teaching methods, which lack variation, lead to decreased enthusiasm among students in the learning process. This study aims to examine the implementation of varied teaching strategies through Problem-Based Learning (PBL) as an effort to enhance students' motivation. PBL presents students with real-life challenges that need to be solved, which can increase their active participation, engagement, and motivation. By incorporating diverse teaching strategies through PBL, it is expected that students will become more motivated and involved in the learning process, leading to improved academic outcomes. This study is hoped to offer practical solutions for teachers to create more engaging learning environments and boost students' learning motivation in the classroom.